2019
DOI: 10.1016/j.jtcvs.2018.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Increased mortality, morbidities, and costs after heart transplantation in heterotaxy syndrome and other complex situs arrangements

Abstract: Objectives: Heart transplantation (HT) in children with heterotaxy may be affected by anomalous cardiac position, venous return, and splenic function. Outcomes are not well described. We compared post-HT outcomes, including survival and resource utilization, among recipients with congenital heart disease (CHD) in the presence and absence of heterotaxy. Methods: Using linked Pediatric Health Information System and Scientific Registry of Transplant Recipients data (2001-2016), we identified 177 HT recipients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…This effort has allowed for novel analyses that would not be possible with either database in isolation. This includes an in‐depth assessment of costs and resource utilization, assessment of practice variation, and the ability to identify and describe outcomes for subpopulations of interest . We anticipate that the extension of this linkage to include other pediatric solid organ transplants will similarly expand analytic possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…This effort has allowed for novel analyses that would not be possible with either database in isolation. This includes an in‐depth assessment of costs and resource utilization, assessment of practice variation, and the ability to identify and describe outcomes for subpopulations of interest . We anticipate that the extension of this linkage to include other pediatric solid organ transplants will similarly expand analytic possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only two patients were diagnosed as HLHS in the present study, and one had Fontan take-down and one experienced prolonged postoperative recovery. Some studies found that heterotaxy was a risk factor for haemodynamic instability and poor prognosis in Fontan patients [ 18 , 19 ]. During this work, the incidence of heterotaxy in prolonged recovery group was higher than that in standard recovery group (17.1% vs 8.5%, P = 0.042).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, anastomosis of abnormal venae cavae to the normal donor heart is technically demanding and has higher morbidity and mortality. 557 In Japan, to date there has been only one heart transplantation for a patient with single-ventricular physiology. 558 There is no established surgical method for these vascular abnormalities.…”
Section: Cardiac Transplantationmentioning
confidence: 99%